Analysis of the Quality of Ecoenzymes and Their Effect on the Growth of Mustard Greens (Brassica juncea L.) - Fatimatuz Zuhro; Hasni Ummul Hasanah; Lila Maharani (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2023)
Making ecoenzymes is one of the solutions to reduce the quantity of organic waste which has been increasing lately. Ecoenzymes are liquid extract products produced from fermentation of vegetable and fruit residues with brown sugar or molasses as a substrate. Types of vegetables and fruits used as ecoenzyme ingredients can affect the levels of minerals or nutrients contained in ecoenzymes. Information about this will be an important consideration in the process of making ecoenzymes as Liquid Organic Fertilizer. This study aims to determine the quality of ecoenzymes from fruit and vegetable combinations, and to determine the effect of ecoenzymes on the periodic growth of mustard plants. Analysis of the quality of ecoenzymes was carried out through physical and chemical observations using laboratory tests, while analysis of the effect of ecoenzymes was carried out quantitatively by statistical tests using the SPSS application. The results showed that the ecoenzyme liquid contains macro nutrients (N, P, and K), and has a significant effect on the growth parameters of mustard plants.